Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content 1. Requirements for implementing the Green School’s initiative in Public Education Schools in Jeddah Mrs. Fatimah Talal Masrahi, Mrs. Norah Obaid Alshareef, Prof. Najah Mohammed Alsaigh 2. Inclusion of Twenty-First Century Skills in the Books of Digital Skills for Fourth Elementary School in Saudi Arabia Mrs. Haya Ali Alqurini, Prof. Najwa Atyan Al-Muhammadi 3. The Degree to Which the Teachers Who Won the Queen Rania Al-Abdullah Award for Educational Excellence Possess and Practice Twenty-First Century Skills from Their Point of View Mrs. Mohammed Musa Al-Salamat, Dr. Jehad Al-Momeni 4. Spiritual intelligence and its relationship to psychological flow as predictors of psychological quality of life for secondary school teachers in Riyadh Mrs. Hessa Fahd Al-Quraini, Dr. Siham Mahji Al-Mutairi 5. The locus of control and its relationship to psychological anxiety among Individuals Recovering From COVID-19 in Madinah Mrs. Roaa Talal Sagga 6. The Psychological Impact of Bullying on Children’s Personalities and Cognitive Development: A Case Study of Saudi Children Dr. Uhuud fahad Alassaf